Pengaruh Beban Pajak Tangguhan, Book Tax Differences, Karakteristik Perusahaan Terhadap Manajemen Laba - Aryani, Amelia; Ismanto, Juli (UNPERBA, 2024)
This study aims to determine the effect of deferred tax costs, tax accounting differences, and company characteristics on earnings management practices in companies. Research variables include deferred tax expense, accounting tax spread, firm size, leverage, profitability, and company age. The main objective of this study is to understand how these factors influence the tendency of managers to manage earnings. The research method used in this research is empirical research with a quantitative approach. The data used is secondary data obtained from the issuer's financial reports and tax reports in [several countries]. The sampling technique used was purposive sampling, with a sample of the company population that met the search criteria. Data analysis was performed using multiple linear regression to examine the relationship between the independent variables (deferred tax expense, accounting tax difference, company size, leverage, profit, and age companies) companies) and the dependent variable (revenue management practices). . In addition, descriptive statistical analysis is also used to provide insight into the characteristics of the companies in the sample. The results show that deferred tax expense, tax accounting differences, firm size, leverage, profitability, and age have a significant effect on earnings management practices. Deferred tax expense and tax accounting differences are proven to have a positive relationship with earnings management practices, while company size, leverage, profitability and age have positive and negative relationships with earnings management activities. These results provide important information for practitioners, regulators and academics about the factors that influence earnings management practices. Furthermore, the results of this study also highlight the importance of paying attention to tax aspects and the differences between financial reports and tax reports in the corporate decision-making process. This research will contribute to the development of the accounting and finance literature and enhance the understanding of revenue management and its implications in the tax context.